The objectification of therapeutical methods used for improvement of the deep stabilizing spinal system - Malátová, Renata; Pucelík, Jirí; Rokytová, Jitka; Kolár, Pavel (Neuro endocrinology letters, 2007)
OBJECTIVE: Despite the ever ongoing development in the examination procedures, it is still impossible to exactly diagnose a large percentage of patients with vertebral and back (low-back and neck) pains. This is due to an insufficiently clear connection between symptoms, pathological changes and results from the imaging techniques. Besides a morphological and neurological examination, a grave diagnostic attention should be given to a possible muscular dysfunction. A simple electromechanical device called muscle dynamometer (MD01) has been constructed for the purpose of enabling to effortlessly, objectively and precisely examine the muscle power-output in the lumbar spine area and reveal a possible, often found and therapeutically treated, dysfunction of the deep stabilizing spine system (DSSS). METHODS: The six-week-rehabilitation-course, aimed at correcting the body posture and strengthening the DSSS muscles, during which two groups of healthy adolescents (girls and boys, aged 12-16) have been obtained. RESULTS: The statistically significant change (p<0.001) between the values of input and output measurements of the condition of DSSS. CONCLUSIONS: The effectiveness of therapeutical training is confirmed and the objectification of the condition of the DSSS muscles by means of the muscle dynamometer (MD01) is verified.
Keywords: Male; svalová síla - dynamometr; bolest krku; Palpation; Adolescent; Child; dítě; mužské pohlaví; Neck Pain; palpace; svalová síla; mladiství; Muscle Strength Dynamometer; Muscle Strength; lidé; Low Back Pain; ženské pohlaví; Humans; Lumbar Vertebrae; lumbalgie; Female; bederní obratle